Iron status of Asian children aged 2 years living in England. Issue 5 (1st May 1998) - Lawson, M S; Thomas, M; Hardiman, A
Abstract : Haemoglobin and ferritin values were analysed in blood from 1057 children, aged 2 years, of Asian parents living in England. Children who had thalassaemia trait or a current/recent infection were excluded. Twenty nine per cent of Pakistani, 25% of Bangladeshi, and 20% of Indian children had haemoglobin < 110.0 g/l. The recent national diet and nutrition survey of preschool children found a prevalence of 12% of 2 year olds with haemoglobin < 110.0 g/l. No single factor accounted for more than a small proportion of the variance in haemoglobin and ferritin values, but the most significant factors that had a negative effect on iron status included the amount of cows' milk consumed, the use of a baby bottle, and mother's place of birth being outside of the UK. Taking vitamin or iron supplements was positively associated with iron status in one or more of the three groups.